Environmental effectiveness of GAEC cross-compliance Standard 4.1 (b, c) ‘Protection of permanent pasture land’ and economic evaluation of the competitiveness gap for farmers - Salis, Mauro; Sepe, Lucia; Francaviglia, Rosa; Fedrizzi, Marco; Bazzoffi, Paolo; Claps, Salvatore; Pitzalis, Maurizio; Lilliu, Michele; Ruda, Paola; Sabia, Emilio; Bruno, Annarita; Rufrano, Domenico; et al. (Italian Journal of Agronomy, 2015)
The paper presents the main results of the monitoring on the effectiveness of the cross-compliance Standard 4.1 ‘Permanent pasture protection: lett. b, c’ carried out in two case studies within the project MO.NA.CO. Soil, botanical, productive and economic (competitiveness gap) parameters have been monitored. In the short term, the Standard 4.1 showed its effectiveness on soil quality, biomass productivity and competitiveness gap in both case studies. Botanical parameters showed differing results, therefore their generalization is not applicable to the heterogeneity of the pasture land Italian system. Shallow soil tillage could be suggested, every 40-50 years, when an appropriate soil organic matter content and the absence of runoff phenomena occur.